A new species of marsupial frog of the genus Gastrotheca Fitzinger (Anura: Amphignatodontidae) from the State of Bahia, Northeastern Brazil - Juncá, Flora Acuña; Nunes, Ivan (Zootaxa, 2008)
A new species of Gastrotheca is described from Serra da Jibóia, Municipality of Santa Terezinha, State of Bahia, Northeastern Brazil. Gastrotheca flamma sp. nov. is characterized by the following combination of traits: SVL 55.3 mm; skin on dorsum weakly granulate; skin adherent on head; snout truncate in dorsal view and nearly vertical in profile; tympanum rounded; presence of two small supraocular tubercles (anterior tubercle bigger than posterior one); webbing poorly developed between fingers II-III and III-IV; calcars present; distinct color pattern. Comments on species habitat are provided.